Alpha Lipoic Acid Inhibits Expression of Intercellular Adhesion Molecule-1 (ICAM-1) in Type 2 Diabetic Mellitus Rat Models - Ismawati Ismawati; Enikarmila Asni; Mukhyarjon Mukhyarjon; Ilhami Romus (The Indonesian Biomedical Journal, 2020)
BACKGROUND: Diabetes mellitus (DM) is associated with an accelerated atherosclerotic macrovascular disease affecting medium-sized arteries. Several evidences support the role of oxidative stress in atherogenesis. However, the role of alpha lipoic acid (ALA) to prevent atherosclerosis is still debatable. This study was conducted to determine the effect of 60 mg/kg/day ALA for 21 days toward the expression of intercellular adhesion molecule-1 (ICAM-1) in rat model.METHODS: Eighteen male rats were divided into three groups labelled as control group, type 2 DM (T2DM) group, and T2DM+ALA group. The T2DM rat models were created by intraperitoneally injecting 50 mg/kg streptozotocin, followed by 110 mg/kg nicotinamide. Immunohistochemistry was used to evaluate the ICAM- 1 expression in rats. Quantitative image analysis of immunohistochemical stains was done on the abdominal aorta using Adobe Photoshop CS3 to find the area percentage and intensity. Kruskal-Wallis and Mann-Whitney tests were used to compare the mean value of area percentage and intensity.RESULTS: There was an increase in area percentage and intensity of ICAM-1 expression. The highest area percentage of ICAM-1 expression was found in the DM group, while the lowest was found in the control group. There were significant differences in the area percentage and intensity between DM+ALA group and DM group, where the area percentage and intensity of ICAM-I in DM group was higher than the DM+ALA group.CONCLUSION: In conclusion, our results demonstrate that ALA inhibits the expression of ICAM-1 in T2DM rat models.KEYWORDS: atherosclerosis, ICAM-1, alpha lipoic acid